(untitled) (CIPEEX, 2022)
ANXIETY CAN BE UNDERSTOOD FROM DIFFERENT PERSPECTIVES, AS A PHYSIOLOGICAL RESPONSE OF THE ORGANISM TRIGGERED BY STRESSFUL EVENTS, OR AS AN EXAGGERATED RESPONSE TO EVERYDAY EVENTS THAT WOULD NOT BE CATEGORIZED AS STRESSORS, CHARACTERIZING A DISORDER. FOR THE TREATMENT OF ANXIETY-RELATED DISORDERS DRUG TREATMENTS ARE USED AND NON-DRUG TREATMENTS ASSOCIATED WITH IT, SUCH AS PHYSICAL ACTIVITY AND DIETARY CHANGE. HOWEVER, MANY OF THESE DRUGS HAVE UNWANTED ADVERSE EFFECTS, WHICH LEADS THE PATIENT TO LOOK FOR NEW ALTERNATIVES. IN THIS SCENARIO, THE USE OF PHYTOTHERAPICS ARISES. THE PRESENT SYSTEMATIC REVIEW WITH STATISTICAL META-ANALYSIS AIMED TO VERIFY WHETHER THE USE OF HERBAL MEDICINE IS DIRECTLY LINKED TO THE RELIEF OF ANXIETY SYMPTOMS IN RESEARCH CARRIED OUT BETWEEN 2015 AND 2021 AND EXPLANATORY NATURE IN DIFFERENT BASES OF SCIENTIFIC DATA. AMONG THE HERBAL MEDICINES WITH A CARMINATIVE EFFECT ARE VALERIAN (VALERIANA OFFICINALIS), AND CHAMOMILE (MATRICARIA CHAMOMILLA), LEMON BALM (MELISSA OFFICINALIS) AND LEMONGRASS (CYMBOPOGON CITRATUS) THAT CAN TREAT PASSION FRUIT (PASSIFLORA EDULIS), AND IN CASES OF INSOMNIA, HAWTHORN (CRATAEGUS LAEVIGATA) AND HOPS (HUMULUS LUPULUS) ARE ALSO INCLUDED, HOWEVER, SOME MEDICINAL SPECIES BELONGING TO THE MYRTACEAE FAMILY, FABACEAE AND ACANTHACEAE WERE MOST PROMINENTLY USED FOR ANXIETY RELIEF. THE MAIN PROPERTIES FOUND FOR THE SPECIES MAINLY OF THE GENERA EUGENIA, MYRCIA AND PSIDIUM THAT HAVE ANTI-INFLAMMATORY, ANTIOXIDANT, ANTIBACTERIAL, ANTICANCER, ACARICIDAL AND ANTIFUNGAL ACTIONS, ESPECIALLY ANTI-INFLAMMATORY, ANTIOXIDANT. WITH THESE VARIABLES, IT WAS POSSIBLE TO MEASURE AND DESCRIBE CHARACTERISTICS ABOUT THE ANXIETY DISORDER, ITS IMPACT ON PEOPLE, AND THE USE OF MEDICINAL PLANTS/HERBAL MEDICINES IN COMPARISON WITH THE USE OF OTHER DRUGS.